2021
DOI: 10.24018/ejfood.2021.3.5.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NPK, Bio-Fertilizers and Manures on Growth of Maize (Zea mays L.) and Soil Nutrients Content in Maiduguri, Nigeria

Abstract: A pot experiment was carried out at screen house, Faculty of Agriculture University of Maiduguri to compare the effect of NPK, bio-fertilizers and manures applications on growth and nutrient uptake by maize. The experiment consisted of 9 treatments of combined application of NPK at half and full recommended rates for maize, Azotobacter chroococcum, Bacillus megaterium and Pseudomonas fluorescence biofertilizers and cow dung and poultry manures and replicated three times in a Completely Randomized Design (CRD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In fact, nutrient application from organic and inorganic sources leads to better nutrients availability and further enhanced the nutrient content in the plants’ stover and grain [ 59 ]. Muazu and Uyovbisere [ 60 ] also reported that manure can boost nutrient uptake; and previous have highlighted that the combined application of nutrients from organic and inorganic source improves N, P and K uptake [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, nutrient application from organic and inorganic sources leads to better nutrients availability and further enhanced the nutrient content in the plants’ stover and grain [ 59 ]. Muazu and Uyovbisere [ 60 ] also reported that manure can boost nutrient uptake; and previous have highlighted that the combined application of nutrients from organic and inorganic source improves N, P and K uptake [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%